The effect of cooperative learning model on cooperation and learning outcomes of futsal playing skills - Nabilah Yaafi'ah Shalihah; Bayu Budi Prakoso; Dwi Lorry Juniarisca; Nanang Indriarsa; Erwin O. Estrella (Universitas Sriwijaya, 2024)
This study aimed to determine the effect of the TGT-type cooperative learning model on students' cooperation and learning outcomes and the relationship between cooperation and students' learning outcomes in playing futsal. This pre-experiment research used One group Pretest-Post-test Design. 29 class X students (16 males and 13 females) were sampled to fill out a cooperation questionnaire and were observed using the Game Performance Assessment Instrument (GPAI) while playing futsal. Descriptive statistical test, normality test, Paired Sample T-test, Wilcoxon Signed Rank, and Product Moment correlation test. The results showed that the value of cooperation increased significantly (t = 5.399, p = 0.000) from the pretest of 147.72 to 156.97 at the post-test, an increase of 6.3%. The value of GPAI increased significantly (Z = -3.375, p = 0.001) from the pretest of 1.362 to 1.458 the post-test increasing by 7.05%. There was no relationship between cooperation and GPAI (r = -0.048, p = 0.804). It is concluded that the TGT-type cooperative learning model can improve students' cooperation and game performance during futsal learning. Cooperation in general does not contribute to learners' performance when playing futsal. The variable of tactical awareness in playing futsal may need to be investigated to determine the adequate cooperation model needed in the game of futsal.